TLC Colombia -Union Europea ¿y qué pasa con Boyacá? - Arcos Soto, Cindy Thatiana; López Cepeda, Michael; Hernández Castro, Haiver; García Ríos, Alfonso (Uptc, 2012)
FTA of Colombia and the EU is a fact. It was signed by our rulers, with or without public participation, in spite of Colombia is a country that is governed by the principles of democracy, which “leads” all processes of development of our nation. This paper examines opportunities, threats and realities that this agreement represents for products, such as meat, milk and its derivatives, as well as the national panorama of import and exports of those articles.